The future of automated capture of social kinesic signals for psychiatric purposes - Burgoon, Judee K.; Elkins, Aaron C.; Derrick, Douglas; Walls, Bradley; Metaxas, Dimitris (Frontiers in Computer Science, 2023)
This article considers how computer vision can be enlisted for biomedical applications, specifically the measurement and treatment of psychiatric disorders. Often, youngsters are too afraid or embarrassed to disclose their emotional and mental problems to therapists. If a system can be utilized not only to collect in a nonthreatening manner ongoing records of a patient’s psychophysiological state but also to analyze and output the periodic results, it may be an efficient and effective means for therapists to plan treatments. We report on various tools for analyzing social kinesic signals for emotional and physiological states but only one, AVATAR, that both captures a patient’s state and also outputs an analysis that flags problem areas for therapists. In this way, automated tools can augment human observation and judgment.